A knight for the runaway nun - Townend, Carol (Townend, Carol. Convent brides., 2023)
"Lady Bernadette is poised to take Holy Orders when Sir Hugo of Nérac, her father's captain of the guards, arrives with news that her sister is expecting. Petrified of childbirth since her mother died, Bernadette races home. But now that she's left the convent, her father wants her wed! There's only one solution" marry Hugo, her childhood friend. But can she risk consummating their marriage and conceiving...even if his kisses are unbearably tempting?"--